Systematics and cladistics of Megalostomis Chevrolat, and the biogeography of Clytrini (Coleoptera: Cryptocephalinae) - Agrain, Federico Alejandro (2011)
We present a cladistic analysis of the subtribe Megalostomina, a Neotropical group of 'case-bearer' leaf beetles. A comparative study of the external and internal adult morphology of Clytrini was undertaken. New characters are described for the subtribe Megalostomina, from the internal sac of aedeagus, which provide a useful phylogenetic signal. More than 180 photographs illustrating the most important characters (74 characters and their respective states) used in the cladistic analysis are provided. The cladistic analysis of 57 terminal taxa and 95 characters was undertaken, under equal weights, and also using implied weights as a means to down-weight homoplasious characters. We test the monophyly and explore intergeneric relationships of the subtribe Megalostomina, and reconstruct the relationships among the species of Megalostomis Chevrolat. The 42 species recognized can be assigned either to a group mostly containing species of North and Central America, or to a larger one of mostly South American species. Support is low, and the formal naming of groups is deferred pending a revision of all Megalostomina. We confirm the subgenera of Megalostomis of previous classifications are unnatural, and the following changes in the generic classification of the subtribe Megalostomina are proposed: Coleorozena Moldenke syn.n. of Coscinoptera Lacordaire; Coleothorpa Moldenke syn.n. of Coscinoptera Lacordaire; and Euryscopa (Coleoguerina) Moldenke syn.n. of Coscinoptera Lacordaire. Furthermore, six formerly recognized subgenera of Megalostomis are considered junior synonyms of Megalostomis Chevrolat: Megalostomis (Minturnia) Lacordaire syn.n.; Megalostomis (Heterostomis) Lacordaire syn.n.; Megalostomis (Scaphigenia) Lacordaire syn.n.; Megalostomis (Snellingia) Moldenke syn.n.; Megalostomis (Coleobyersa) Moldenke syn.n.; and Megalostomis (Pygidiocarina) Moldenke syn.n. Thus, no subgenera are recognized within Megalostomis. Previous hypotheses on Clytrini biogeography were revisited in the light of new biogeographic and phylogenetic knowledge. We hypothesize an origin of Clytrini in tropical/subtropical Gondwana, when South America, Africa, Madagascar and India were connected. Changes in the configuration of the tectonic plates in the Cenozoic allowed the dispersal of Clytrina to the Palaearctic and Nearctic regions, and dispersion of Babiina and Megalostomina through the Nearctic region.